2005
DOI: 10.1634/stemcells.2005-0201
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Homing of Nonmobilized Peripheral-Blood CD34+ Cells After Intracoronary Injection

Abstract: Granulocyte-colony-stimulating factor administered for autologous hematopoietic stem cell isolation from blood may favor restenosis in patients implanted after acute myocardial infarction (AMI). We therefore tested the isolation of peripheral-blood CD34؉ cells without mobilization in six patients with AMI. After large-volume cytapheresis and positive CD34 ؉ cell selection, 3.6 to 27.6 million CD34؉ cells were obtained. We performed intracoronary implantation of these cells and recorded no restenosis or arrhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 19 publications
4
63
0
3
Order By: Relevance
“…Numerous studies have shown that circulating human CD34 1 cells hold great promise for tissue repair and regeneration (25)(26)(27)(28). In fact, a recent clinical trial by Losordo and colleagues demonstrated that administration of autologous CD34 1 cells rendered protection against refractory angina (29).…”
Section: Cd34mentioning
confidence: 99%
“…Numerous studies have shown that circulating human CD34 1 cells hold great promise for tissue repair and regeneration (25)(26)(27)(28). In fact, a recent clinical trial by Losordo and colleagues demonstrated that administration of autologous CD34 1 cells rendered protection against refractory angina (29).…”
Section: Cd34mentioning
confidence: 99%
“…28,29 To date, no human clinical studies have been initiated because of both the ethical issues surrounding access to embryos and the possibility of teratoma formation, suggested by a study injecting ES cells in skeletal muscle. 30 …”
Section: Embryonic Stem Cellmentioning
confidence: 99%
“…18,19 overall, myocardial retention expressed as a percentage of stem cells administered appears to be rather low, with lower retention in chronic Mi and iCMP compared to acute Mi. 15,20,21 Furthermore, there is significant efflux of stem cells from the site of delivery on delayed imaging. in our experience, homing of intracoronarily injected 99m tc-hMPao-labeled Cd34 + stem cells in patients with nonischemic dilated cardiomyopathy is comparable to patients with iCMP, with stem cell retention rates around 1%.…”
Section: Evaluation Of Early Retentionmentioning
confidence: 99%